2012
DOI: 10.2175/106143012x13373550427273
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Degradation by Photolysis and Titanium Dioxide Photocatalysis

Abstract: We investigated the degradation of carbamazepine by photolysis/ultraviolet (UV)-C only and titanium dioxide photocataiysis. The degradation of carbamazepine by UV-only and titanium-dioxideonly (adsorption) reactions were inefficient, however, complete degradation of carbamazepine was observed by titanium dioxide photocataiysis within 30 min. The rate of degradation increased as initial carbamazepine concentration decreased, and the removal i Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 37 publications
2
19
2
Order By: Relevance
“…TiGC kinetics are relatively constant over the range of CBZ concentrations (with 10–15% deviation in the reaction constant), whereas the decomposition rate constant of TiO 2 decreases with an increasing CBZ concentration (more than 80% reduction in the reaction constant). A similar observation was reported by others: a higher CBZ initial concentration suppressed the TiO 2 rate of degradation [ 18 , 52 ]. Im et al proposed that, in a TiO 2 colloidal suspension, excess CBZ molecules accumulate on the TiO 2 surface, suppressing the light absorbance and ROS generation by TiO 2 [ 18 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…TiGC kinetics are relatively constant over the range of CBZ concentrations (with 10–15% deviation in the reaction constant), whereas the decomposition rate constant of TiO 2 decreases with an increasing CBZ concentration (more than 80% reduction in the reaction constant). A similar observation was reported by others: a higher CBZ initial concentration suppressed the TiO 2 rate of degradation [ 18 , 52 ]. Im et al proposed that, in a TiO 2 colloidal suspension, excess CBZ molecules accumulate on the TiO 2 surface, suppressing the light absorbance and ROS generation by TiO 2 [ 18 ].…”
Section: Resultssupporting
confidence: 89%
“…TiO 2 is a widely used heterogeneous and wide bandgap photocatalyst that shows a robust performance and has a low cost. Various studies report the photocatalytic degradation of CBZ by reactive oxygen species (ROS) generated by TiO 2 under UV radiation [ 18 , 19 , 20 ]. However, the influence of environmental factors, such as the presence of natural organic macromolecules (NOM), is often overlooked in evaluating the performance of novel nanomaterials for contaminant removal applications in water.…”
Section: Introductionmentioning
confidence: 99%
“…S et al, 2009). At pH values more acidic than PZC (Im. J.K et al, 2012), the ZnO particle will be positively charged and attraction will be enhanced for anionic molecules.…”
Section: Iii11 Hydrogen Potential (Ph)mentioning
confidence: 99%
“…In the case of solid solutions (Bakiz et al, 2018; Hallaoui et al, 2016; Taoufyq et al, 2015), the chemical substitution allowed modifying the energies and intensities of photoluminescence emissions, acting as structural defects, mainly oxygen vacancies.Other authors have shown the role of charge separation or the polarization on photocatalytic activity and photoluminescence emissions (Chen, Huang, Guo, Zhang, & Ma, 2019; Chen et al, 2018; Hao et al, 2019; Huang et al, 2017). Other compounds such as TiO 2 (Im, Son, Kang, & Zoh, 2012), ZnO (Tanveer, Guyer, & Abbas, 2019), Bi 2 MoO 6 (Bi et al, 2007), BaSO 4 (Cui et al, 2019), Ag 3 PO 4 (Ge, 2014), Na 3 Bi 2 (PO 4 ) 3 (Huang, Chen, & Zhang, 2014), Zn 3 (PO 4 ) 2 (Naciri et al, 2018), Mn 3 (PO 4 ) 2 (Bouddouch et al, 2019), and BiVO 4 (Zhou et al, 2006)were also studied. Recently, we have developed studies on phosphate‐based phases for electrocatalytic applications (Chennah, Naciri, Ahsaine, et al, 2018; Chennah, Naciri, Taoufyq, et al, 2018; Ghalwa & Zaggout, 2006).…”
Section: Introductionmentioning
confidence: 99%